Attentional ability among survivors of leukaemia treated without cranial irradiation. Issue 2 (1st February 2003) - Rodgers, J; Marckus, R; Kearns, P; Windebank, K
Abstract : Background: Previous research has indicated that children who have received treatment for leukaemia which includes cranial irradiation exhibit deficits in their ability to focus attention. It has been suggested that the use of cranial irradiation may have a role to play in long term sequelae. Aims: To investigate neuropsychological functioning among children treated for leukaemia without cranial irradiation. Methods: In a cross sectional study, 17 leukaemic patients and their sibling controls were assessed using a neuropsychological model of attention. All were treated on the UKALL XI protocol and none had received cranial irradiation. Participants completed the Arithmetic subtest and Digit Span subtest of the Weschler Intelligence Scale for Children–Revised to assess focus–encode elements of attention; the Coding subtest and the Speed of Information subtest of the BAS to assess focus–execute aspects of attention; the VIGIL computerised battery to assess sustain elements of attention; and the Wisconsin Card Sorting test to assess the ability to shift attention. Results: These children did not exhibit the deficits witnessed in previous cohorts, and were performing at comparable levels to their controls on all measures of attention Conclusions: These findings suggest that children who have received treatment for leukaemia without the use of cranial irradiation do not show the neuropsychological insult found in earlier treatment groups.